Juridical Review of Name Loan Agreements in Controlling Property Rights to Land in Indonesia - Afriyati Wahyningrum (Sultan Agung Notary Law Review, 2020)
This research is entitled Juridical Review of Name Loan Agreement (Nominee) in Ownership of Land in Indonesia. This research aims to find out (1) a juridical review of ownership rights over land of foreign citizens in investment activities in Indonesia and (2) the legal status or consequences of foreign citizens in investing in Indonesia. The problem in this research is the inequality between ideality and reality. There are still many practices of controlling ownership of land by foreign citizens through Nominee Agreements using the guise of Indonesian citizens so that it seems as if they do not violate the law. Even this action was legalized by the Notary/PPAT who in fact clearly understood the applicable law. This study uses a normative juridical approach. The method used in data processing and data analysis used in this study is a qualitative method, which is a descriptive analytical data analysis method that refers to a particular problem or is based on applicable laws and regulations. The results of this study indicate that the making of deeds made by notaries regarding land sale and purchase by borrowing name or nominee agrement is null and void for the sake of law this violates the Civil Code articles 1335 and 1337 of the Civil Code and article 33 paragraph (3) of the 1945 Constitution and Article 21 paragraph (1) and 26 paragraphs (20 UUPA, also violate the rights of the Indonesian people over Indonesian territory. that is, a descriptive analytical data analysis method that refers to a particular problem or is based on the prevailing laws and regulations. The results of this study indicate that the making of deeds made by notaries regarding land sale and purchase by borrowing name or nominee agrement is null and void for the sake of law this violates the Civil Code articles 1335 and 1337 of the Civil Code and article 33 paragraph (3) of the 1945 Constitution and Article 21 paragraph (1) and 26 paragraphs (20 UUPA, also violate the rights of the Indonesian people over Indonesian territory. that is, a descriptive analytical data analysis method that refers to a particular problem or is based on the prevailing laws and regulations. The results of this study indicate that the making of deeds made by notaries regarding land sale and purchase by borrowing name or nominee agrement is null and void for the sake of law this violates the Civil Code articles 1335 and 1337 of the Civil Code and article 33 paragraph (3) of the 1945 Constitution and Article 21 paragraph (1) and 26 paragraphs (20 UUPA, also violate the rights of the Indonesian people over Indonesian territory.